LEARNING TO WRITE INSPIRATIONAL STORY TEXTS THROUGH INTERACTIVE VIDEOS BASED ON A DEEP LEARNING APPROACH - Suwantika, Deby Amelia (Universitas Tanjungpura, 2026)
Indonesian language learning at the junior high school level, particularly in writing inspirational narrative texts, continues to face several challenges. Many students struggle to generate ideas, construct coherent plotlines, and choose appropriate diction, resulting in monotonous and less engaging writing. This study is a literature review employing a descriptive qualitative approach following the PRISMA framework to examine research on the integration of interactive videos and deep learning approaches in improving students’ writing skills. The review process included article identification, eligibility screening, and thematic analysis of relevant studies. The synthesis reveals that interactive videos help students build imagination, generate ideas more quickly, and understand narrative structures, while deep learning encourages critical and reflective thinking, enabling them to produce more coherent and meaningful texts. This study is limited by the number of included articles and the diversity of research contexts. Therefore, classroom implementation should involve careful selection of relevant videos, consistent teacher guidance, and further studies encompassing broader contexts.